The The Qur’an Reception within Dauroh Tahfidz Al-Qur’an of SDI Al-Azhaar Students Tulungagung - Ubaidillah Hasan; Lalak Lailathus Saqdiah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2024)
The tradition of memorizing Al-Qur’an in SDI Al-Azhaar is more than just a fatalistic attitude and mentality but also a social achievement in the case of paying attention to memorization aspects; memorizing the Qur’an quickly and correctly. The Qur’an tradition personally gives unique and diverse experiences. It gives the inherent meaning of each Hafizh Qur’an. This study aims to explain how the phenomenon of living Qur'an in dauroh tahfidz Al-Qur’an. This research uses the data collection techniques are observation, interviews, and documentation Milles and Huberman. The approaches used are the sociological theory of Karl Manheim and the traditional actions of Max Weber. The results of this study are first, the activities of dauroh tahfidz Al-Qur’an must be followed by the accelerated students every semester break, second, sociologically the activities of dauroh tahfidz Al-Qur’an has an objective meaning as a symbol of obeying the teacher’s words meanwhile the traditional action as a habit that has been passed down for generations. Expressively these activities also show the changing of students’ psychology for the better. It is realized through the calm feeling of students. Meanwhile, effective action can be solace. Documentarily those activities form a comprehensive cultural system that needs to be preserved, whereas in instrumental rationalist action the students begin to realize the importance of dauroh tahfidz Al-Qur’an to finish the goal of memorizing 30 juz.